CpG dinucleotides and the mutation rate of non-CpG DNA - Walser, Jean-Claude; Ponger, Loïc; Furano, Anthony V. (Genome Research, 2008)
The neutral mutation rate is equal to the base substitution rate when the latter is not affected by natural selection. Differences between these rates may reveal that factors such as natural selection, linkage, or a mutator locus are affecting a given sequence. We examined the neutral base substitution rate by measuring the sequence divergence of ∼30,000 pairs of inactive orthologous L1 retrotransposon sequences interspersed throughout the human and chimpanzee genomes. In contrast to other studies, we related ortholog divergence to the time (age) that the L1 sequences resided in the genome prior to the chimpanzee and human speciation. As expected, the younger orthologs contained more hypermutable CpGs than the older ones because of their conversion to TpGs (and CpAs). Consequently, the younger orthologs accumulated more CpG mutations than the older ones during the ∼5 million years since the human and chimpanzee lineages separated. But during this same time, the younger orthologs also accumulated more non-CpG mutations than the older ones. In fact, non-CpG and CpG mutations showed an almost perfect (R2 = 0.98) correlation for ∼97% of the ortholog pairs. The correlation is independent of G + C content, recombination rate, and chromosomal location. Therefore, it likely reflects an intrinsic effect of CpGs, or mutations thereof, on non-CpG DNA rather than the joint manifestation of the chromosomal environment. The CpG effect is not uniform for all regions of non-CpG DNA. Therefore, the mutation rate of non-CpG DNA is contingent to varying extents on local CpG content. Aside from their implications for mutational mechanisms, these results indicate that a precise determination of a uniform genome-wide neutral mutation rate may not be attainable.
10.1101/gr.076455.108